2019
DOI: 10.11591/edulearn.v13i1.11189
|View full text |Cite
|
Sign up to set email alerts
|

The influence of project-based learning strategies on the metacognitive skills, concept understanding and retention of senior high school students

Abstract: Biology learning in the 21st century leads to the empowerment of metacognitive skills. Increased metacognitive skills can support concept understanding and maximize the students' retention of concepts. This research aimed at investigating the effect of project-based learning strategy on metacognitive skills, concept understanding and retention of class X students of Senior High School 1 Kairatu, West Seram District, Maluku. This research is a quasi-experimental research using pre test-post test nonequivalent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
(8 reference statements)
2
14
0
1
Order By: Relevance
“…The rubric included eight measures (0-7), which were used to evaluate students' responses to each test item. According to Green [49], the levels of metacognitive skills are as: "super (85-100), ok (68-84), development (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67), cannot really (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), risk (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rubric included eight measures (0-7), which were used to evaluate students' responses to each test item. According to Green [49], the levels of metacognitive skills are as: "super (85-100), ok (68-84), development (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67), cannot really (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), risk (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)…”
Section: Data Collectionmentioning
confidence: 99%
“…Research results related to metacognitive skills and scientific attitudes in Indonesia's learning process are still relatively low. The research conducted in senior high schools reported that students' metacognitive skills were categorized as low [36]. Other research results also show that relatively university-level metacognitive skills are still low [37].…”
mentioning
confidence: 99%
“…After going through the learning process, students' understanding of plant motion material has increased. Rumahlatu & Sangur (2019) also explain that learning outcomes are related to students' understanding of a concept formed through the learning process (contextual). It can be seen in the research conducted by Anisa et al (2018) regarding readiness for independent study.…”
Section: Learning Outcomesmentioning
confidence: 99%
“…The higher the students' retention is, the better the students' ability to store information well and retrieve it for the next activity (Wicaksono & Corebima, 2015). Similarly, Rumahlatu & Sangur (2019) state that students' retention will be stronger if students have meaningful learning experiences. The activities of the CITP learning process provide opportunities for students to empower their retention.…”
Section: The Effect Of Learning Models On Students' Retentionmentioning
confidence: 99%